2020
DOI: 10.1097/brs.0000000000003866
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for a Dual Attending Surgeon Strategy in Posterior Spinal Fusion (PSF)

Abstract: Study Design. Retrospective study. Objective. To assess the learning curve of a dual attending surgeon strategy in severe adolescent idiopathic scoliosis patients. Summary of Background Data. The advantages of a dual attending surgeon strategy in improving the perioperative outcome in scoliosis surgery had been reported. However, the learning curve of this strategy in severe scoliosis had not been widely stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In this retrospective study, the utilization of DCMS demonstrated shorter operative times, reduced blood loss, and shorter hospital stays compared to TCT. Excessive bleeding and prolonged anesthesia time are highlighted as factors contributing to perioperative complications [22][23][24]. For instance, prolonged hypotension resulting from signi cant blood loss during surgery poses a risk factor for neurological complications [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective study, the utilization of DCMS demonstrated shorter operative times, reduced blood loss, and shorter hospital stays compared to TCT. Excessive bleeding and prolonged anesthesia time are highlighted as factors contributing to perioperative complications [22][23][24]. For instance, prolonged hypotension resulting from signi cant blood loss during surgery poses a risk factor for neurological complications [25].…”
Section: Discussionmentioning
confidence: 99%